EFFECTS OF OBESITY ON THE SERUM BMP15, GDF9, AND KISSPEPTIN CONCENTRATIONS IN WOMEN OF REPRODUCTIVE AGE: OBESITY ON THE SERUM BMP15, GDF9, AND KISSPEPTIN - BULUT ARIKAN, Funda; SAGSOZ, Nevin (Journal of Medical Biochemistry, 2022)
Background: As BMP15, GDF9, and kisspeptin all play critical roles in folliculogenesis and fertilization, investigating the possible relationship between obesity and these three factors could prove crucial in relation to understanding the role of obesity in infertility. Thus, the present study sought to determine the effects of obesity on the serum BMP15, GDF9, and kisspeptin concentrations in women of reproductive age.Methods: Ninety female participants were equally divided into three groups: class-1 obese (n=30), class-2 obese (n=30), and normal weight (control; n=30). The participants’ serum BMP15, GDF9, and AMH concentrations were measured. Moreover, the serum kisspeptin concentrations were evaluated in the class-1 obese and control groups by means the enzyme-linked immunosorbent assay (ELISA) method while the participants were in the menstrual period.Results: The serum BMP15 and kisspeptin concentrations were found to be much higher in the control group than in both obese groups (p=0.001 and p=0.01, respectively). While the GDF9 concentration exhibited statistically significantly positive correlation with age, the BMP15 concentration exhibited positive correlation with both the kisspeptin and LH concentrations in the control group. In addition, positive correlation was identified between the BMP15 concentration and both age and the glucose level, as well as negative correlation with the insulin level, in both the obese groups.Conclusions: Obesity appears to reduce the serum BMP15 and kisspeptin concentrations in obese women of reproductive age. This reduction may represent a milestone in terms of reproductive dysfunction, and it may be used to predict the success of infertility treatment in obese women.
Keywords: Obesity, BMP15, GDF9, Kisspeptin, Reproductive